Effect of sildenafil citrate in testosterone induced benign prostate hyperplasia rat model - ERCAN, FERİHA (AVES, 2017)
Objective: Efficacy of treatments for benign prostate hyperplasia (BPH) is limited because the disease has complex etiopathogenesis. Recent studies have demonstrated the presence of phosphodiesterase-5 (PDE-5) receptors in prostate tissue. We investigated efficacy of sildenafil citrate in testosteron -induced BPH in rats. Material and methods: The rats were divided into three groups. Each groups had 7 rats. Group 1 was control group. Testosteron propionate 3 mg/kg/day was injected subcutaneously for two weeks in Group 2. The same procedure was done for Group 3 and sildenafil citrate was added to water at daily doses of 2 mg/kg for two weeks. The rats were euthanized with intraperitoneal pentobarbital. The body weights were measured and the prostates were removed. Results: The mean weights of rats were 288+/-31.93, 345+/-23.23 and 294+/-32.86 g in Groups 1, 2 and 3, respectively. The mean prostate weights of rats were 0.74+/-0.18, 1.3+/-0.13 and 0.72+/-0.24 g in Groups 1, 2, and 3, respectively. Group 2 had statistically significantly higher prostate weights than the other groups (p<0.01). Relative prostate weight is calculated with ratio of prostate weight to body weight. BPH group showed an increase in relative prostate weight compared with other groups with significant difference (p=0.036 and p=0.040). There was statistical difference for acinar area between Group 2 and the others, no significant difference of number of acini, interstitial space and epithelial thickness. Group 2 has more papillary projections per acini than the other groups. Conclusion: Favourable effect of sildenafil citrate on dimensions of prostate but not all on histological parameters was observed. We expect that PDE-5 inhibitors might be a treatment option for BPH patients if the studies support our findings in the future.
Keywords: Hyperplasia; prostate; sildenafil citrate; PHOSPHODIESTERASE-5; RELAXATION; URETHRA; INHIBITION; ISOENZYMES; BLADDER